The Relationship between Change Leadership Practices and Organizational Commitment in the Faculty of Education, University of Khartoum, Sudan - Saifaldin Idris Onia (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2022)
This study aimed to investigate the relationship between change leadership practices and staffs' organizational commitment at the Faculty of Education University of Khartoum. To achieve the purpose of the study, a survey research design was employed. Among 239 staff members at the Faculty of Education University of Khartoum, data were collected from 106 (44.00%) respondents using close-ended questionnaire. Data collected were analyzed using one sample t-test and Pearson correlation coefficient. The result of the study indicated that the Faculty of Education University of Khartoum has practiced change leadership. The study revealed that the level of staff organizational commitment at the Faculty of Education University of Khartoum was high. Furthermore, the study's findings indicated that change leadership practices had a positive and low relationship with staffs' organizational commitment at the Faculty of Education University of Khartoum. Besides, the study recommended that change leadership practices need to have committed staff members to achieve change vision and goals effectively. As a result, university leaders and researchers should consider the staff's commitment while trying to introduce change initiatives or design change strategies in the university.